The genome of African yam (Dioscorea cayenensis‐rotundata complex) hosts endogenous sequences from four distinct badnavirus species. (15th April 2014) - Umber, Marie; Filloux, Denis; Muller, Emmanuelle; Laboureau, Nathalie; Galzi, Serge; Roumagnac, Philippe; Iskra‐Caruana, Marie‐Line; Pavis, Claudie; Teycheney, Pierre‐Yves; Seal, Susan E.
Summary Several endogenous viral elements (EVEs) have been identified in plant genomes, including endogenous pararetroviruses (EPRVs). Here, we report the first characterization of EPRV sequences in the genome of African yam of the Dioscorea cayenensis‐rotundata complex. We propose that these sequences should be termed 'endogenous Dioscorea bacilliform viruses' (eDBVs). Molecular characterization of eDBVs shows that they constitute sequences originating from various parts of badnavirus genomes, resulting in a mosaic structure that is typical of most EPRVs characterized to date. Using complementary molecular approaches, we show that eDBVs belong to at least four distinct Badnavirus species, indicating multiple, independent, endogenization events. Phylogenetic analyses of eDBVs support and enrich the current taxonomy of yam badnaviruses and lead to the characterization of a new Badnavirus species in yam. The impact of eDBVs on diagnosis, yam germplasm conservation and movement, and breeding is discussed.